Tata Cara dan Proses Pelaksanaan dan Dokumen Akreditasi Sekolah atau Madrasah - Nur Melinda; Muhammad Saupiyani; Husnul Yaqin; Hilmi Mizani (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to comprehensively analyze the implementation mechanism and documentation requirements for school or madrasah accreditation in Indonesia based on the latest regulations. Accreditation is positioned as a vital instrument in guaranteeing educational quality and a form of public accountability to measure the eligibility of educational units according to the National Education Standards (SNP). The research method used is library research by examining various literatures, regulations such as Law No. 20 of 2003 and Permendikbudristek No. 38 of 2023, as well as technical operational documents from the National Accreditation Board for Early Childhood Education, Primary Education, and Secondary Education (BAN-PDM). The results show that the accreditation process has transformed from administrative assessment (compliance) to performance-based assessment through the use of the IASP instrument. The accreditation implementation cycle consists of systematic stages including: (1) identification and targeting, (2) socialization, (3) pre-visitation, (4) visitation and assessment, (5) validation of results, (6) determination of results, and (7) socialization of accreditation results. Furthermore, the effectiveness of accreditation highly depends on the readiness of supporting documents in four main components: graduate quality, learning process, teacher quality, and school management. The conclusion of this study confirms that a deep understanding of procedures and document completeness is not merely a bureaucratic burden, but a means of self-evaluation for educational institutions to carry out continuous quality improvement for the advancement of the education ecosystem in Indonesia.